RESPONSE OF SEA SURFACE TEMPERATURE (SST) AND CHLOROPHYLL-A ON MADDEN JULIAN OSCILLATION (MJO) IN INDONESIAN SEAS - Nabil; Atmadipoera, Agus Saleh; Koropitan, Alan Frendy (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
Madden-Julian Oscillation (MJO) is a large-scale phenomenon that occurs in equatorial area, parti-cularly Indonesia. This research aimed to investigate the MJO propagation process and studied the correlation between MJO and sea surface temperature (SST) and chlorophyll-a. Sea variables (SST and chlorophyll-a) and atmosphere variables (outgoing longwave radiation/OLR, 1,5 km wind, and surface wind) were band-pass filtered for 20-100 days period. Spectral density from OLR and 1,5 km wind (2003-2012) shows that the MJO period was dominantly occurred for 40–50 days. Average pro-pagation of  MJO velocity resulted from the atmospheric variable analysis by Hovmöller diagram was 4,7 m/s. Cross correlation between SST and OLR in South Java and Banda Sea results a strong corre-lation during MJO active phase, where MJO took  place first and was then followed by the decreasing SST along the equatorial region. Increasing chlorophyll-a concentration occured at some areas du-ring MJO active phase with relatively short phase delay. During the MJO active phase, fluctuation of wind velocity generates variation over mixed layer depth and triggers upwelling /entrainment. Nutri-ent was upwelled to the water surface and hence increase phytoplankton production and chlorophyll-a concentration. Keywords: Madden Julian Oscillation, OLR, sea surface temperature, surface chlorophyll-a